Pain and Gain Implementing No Child Left Behind in Three States, 2004-2006 - Stecher, Brian M. (RAND Corporation, 2008)
The Implementing Standards-Based Accountability (ISBA) study was designed to examine the strategies that states, districts, and schools are using to implement standards-based accountability under the No Child Left Behind Act (NCLB). This monograph presents information regarding the implementation of NCLB in California, Georgia, and Pennsylvania from 2003-2004 through 2005-2006, including the final results of the ISBA project.